Establishing a Conditional Peace Treaty on the Basis of the Legend of the Horatii and Curiatii (Liv. 1.24) - Leraczyk, Izabela (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article presents the issue of establishing a conditional (condicio) peace treaty (foedus) on the basis of the legend of the Horatii and Curiatii, as depicted by Livy or Dionysius of Halicarnassus, among others. The condition stipulated that the fate of the war would be decided by a combat between the representatives of the two sides, and the victor would take full military leadership over the defeated side’s army. The text also refers to the concept of the so-called monomachia, that is a single combat of the chosen warriors, which, according to the ancient tradition, might end the battle.